Empirical analysis of export trade patterns from China to Latin America - Zhong, Xiwei; Wang, Honghui Wang (Sinología hispánica. China Studies Review, 2020)
In recent years, the relations between China and Latin America have experienced a dramatic deepening. Latin America is expected to become the last part of the magnificent "The Belt and Road" development program, in order to achieve a new historic opportunity for commercial cooperation between China and Latin America. In this case, it is necessary to carry out a deeper analysis of the export potential between the two parties. First, from a historical perspective, this work analyses the development and current situation of trade between China and Latin America, the structure of commodities of export from China to Latin America and the distribution of the country through the UN statistical database. Then analyses the competitiveness and trade complementarity between China and the main Latin American countries using the formula. According to the results, since the 20th century the import and export trade between China and Latin America has grown vigorously, but the growth rate has slowed and has even declined in recent years. Between China and Latin American countries there is a strong degree of complementarity in trade, but this degree has shown a downward trend. Among Latin American countries, Mexico is the country that dominates the highest competitiveness and the least narrow trade link with China; While Venezuela, Peru and Chile are the countries that maintain the greatest complementarity and the strongest trade link with China. Finally, this work proposes welltargeted policy recommendations.